Enhanced Concanavalin A Binding to Preorganized Mannose Nanoarrays in Glycodendrimersomes Revealed Multivalent Interactions. (4th March 2021) - Yu. Kostina, Nina; Söder, Dominik; Haraszti, Tamás; Xiao, Qi; Rahimi, Khosrow; Partridge, Benjamin E.; Klein, Michael L.; Percec, Virgil; Rodriguez‐Emmenegger, Cesar
Abstract: The effect of the two‐dimensional glycan display on glycan‐lectin recognition remains poorly understood despite the importance of these interactions in a plethora of cellular processes, in (patho)physiology, as well as its potential for advanced therapeutics. Faced with this challenge we utilized glycodendrimersomes, a type of synthetic vesicles whose membrane mimics the surface of a cell and offers a means to probe the carbohydrate biological activity. These single‐component vesicles were formed by the self‐assembly of sequence‐defined mannose‐Janus dendrimers, which serve as surrogates for glycolipids. Using atomic force microscopy and molecular modeling we demonstrated that even mannose, a monosaccharide, was capable of organizing the sugar moieties into periodic nanoarrays without the need of the formation of liquid‐ordered phases as assumed necessary for rafts. Kinetics studies of Concanavalin A binding revealed that those nanoarrays resulted in a new effective ligand yielding a ten‐fold increase in the kinetic and thermodynamic constant of association. Abstract : Multivalent interactions mediated by the cellular glycocalix are ubiquitous in biological processes. We utilized glycodendrimersomes, a type of synthetic cell membrane mimic to probe the carbohydrate biological activity towards lectins. We demonstrated that mannose could organize the sugar moieties into periodic nanoarrays resulting in a new effective ligand yielding a ten‐fold increase in the kinetic and thermodynamic constant of association.